A short review of discovery and development of fish sperm cryopreservation - Dian Afriani; Kartini Eriani; Zainal Abidin Muchlisin; Iwan Hasri (Depik, 2021)
Global biodiversity, especially fish, has experienced a decline, this occurs as a result of over-exploitation, the presence of introduced fish species and climate change. This condition makes researchers look for solutions to overcome these problems by using cryopreservation techniques. The main purpose of cryopreservation is to store, maintain, and ensure the survival of genetic material, so that using cryopreservation techniques can maintain the viability and function of gamete cells both immunologically, biologically and physiologically. The success of the cryopreservation technique has made this technique widely developed in various species of living organism including fish. This article summarizes and reviews the history of the development of cryopreservation of animal species with specific focus on fish.Keywords:CryopreservationHistoryDepikEndemic species